The investigation of influence of starch properties on system water - Пак, Андрій Олегович (Technology audit and production reserves, 2012)
The development of fundamental representations about form, structure and state of water of food systems is topical problem. The kinetics of drying of starch sponge of different molar concentration were investigate by the EPR-method